Simulación numérica de una mezcla bifásica de amoniaco - Hernández Arrieta, Isaac (My University, 2008)
Simulación numérica de una mezcla bifásica de amoniaco
Keywords: Simulación numérica de una mezcla bifásica de amoniaco